Pengawetan Ikan Nila (Oreochromis Niloticus) Menggunakan Daun Sirih Dengan Variasi Lama Perendaman Yang Berbeda - DEVI, ANNA ROOSIANA; , Dra. Titik Suryani, M.Sc (2015)
Tilapia (Oreochromis niloticus) is one of freshwater-culture fish species are favired by the people because the meat is thick and has delicious taste. Tilapia has 84% protein content and low fat content of 2,7%, water content up to 70-80% and 1,2% ash. Tilapia began to decrase its physical quality after two hours of death, this damage can occur according to biochemical or microbiology component. Natural preservations that contain antimicrobial substance such as green-betel leaves and red-betel leaves that actively can inhibit microbial activity. The purpose of this study was to determine the population of bacteria, pH, water content, quality and storability tilapia with a variety of types of natural preservaties and submerged time. The study design using a completely randomized design with teo factors. Factor 1 natural preservaties: green-betel leaves pulp (S1) and red-betel leaves pulp (S2) and the second factor submerged time: 60 minute (L1), 90 minutes (L2) and 120 minute (L3). The results showed that tilapia has best quality in treatment L1S1 (submerged by green-betel leaves pulp for 60 minutes) with a population of bacteria 27 x 150 CFU/g, pH 6.3, and 49% of water content, with power savings for 2 days. Tilapia were submerged by leaves (green and red betel) for 60, 90 and 120 minutes can still be consumed. Keywords: Tilapia, green-betel leaves, red-betel leaves.